On Target? The Israeli Supreme Court and the Expansion of Targeted Killings - Eichensehr, Kristen E. (The Yale law journal, 2007)
Israel has used "targeted killings" against suspected terrorists since the alAqsa intifada began in September 2000. By the end of 2005, almost 300 terrorist organization members and 150 civilian bystanders had been killed in targeted killings, in addition to hundreds of civilians wounded.1 The policy has received wide international condemnation2 and has sparked vigorous debate among scholars about its lawfulness. After four years of consideration,3 the Israeli Supreme Court recently weighed in with the world's first judicial decision on targeted killings in Public Committee Against Torture in Israel v. Government of Israel (PCATI). In PCATI, the court held that terrorists are civilians under the law of armed conflict and thus are lawfully subject to attack only when they directly participate in hostilities.4 But the court also expanded the traditional definition of "direct participation" and the time period during which civilians may lawfully be attacked. By disregarding the "direct participation" requirement's important evidentiary function, the court weakened the protections that international law affords to all civilians, not just to terrorists. [PUBLICATION ABSTRACT]